Right to Fair Hearing in Employment Disciplinary Proceedings Related to Misconduct in Tanzania - Mwita, Kelvin M; Lameck, Matilda (Batulis Civil Law Review, 2023)
Introduction: The right to fair hearing is one of the principles of natural justice that is constitutionally provided for in Tanzania. Number of principal and subsidiary legislations have been enacted to promote the right to fair hearing in employment proceedings. Despite the legal protection, disciplinary proceedings related to misconduct have been persistently decided without affording the accused the right to a fair hearing.Purposes of the Research: The study aimed at examining the gap that exists between the law protecting the right to fair hearing and the actual practice in organisations.Methods of the Research: The study made use of library and field research. Data was collected by using documentary review to collect data from legal documents and published material. Semi-structured interviews were used to collect data from 14 respondents obtained from one of local government authorities in Tanzania.Results of the Research: The study found that existing law have established standards that are capable of promoting the right to fair hearing in disciplinary proceedings. Further, the study observed that there is a gap between law and practice when it comes to promoting the right to fair hearing in disciplinary proceedings related to misconduct. The gap has to do with failure to adequately comply with procedural fairness during hearing. As per the reviewed literature this is the first study to examine the gap between law and practice relating the right to fair hearing with focus on disciplinary proceedings related to misconduct.